mrhl RNA, a Long Noncoding RNA, Negatively Regulates Wnt Signaling through Its Protein Partner Ddx5/p68 in Mouse Spermatogonial Cells - Arun, Gayatri (American Society for Microbiology, 2012)
Meiotic recombination hot spot locus (mrhl) RNA is a nuclear enriched long noncoding RNA encoded in the mouse genome and expressed in testis, liver, spleen, and kidney. mrhl RNA silencing in Gc1-Spg cells, derived from mouse spermatogonial cells, resulted in perturbation of expression of genes belonging to cell adhesion, cell signaling and development, and differentiation, among which many were of the Wnt signaling pathway. A weighted gene coexpression network generated nine coexpression modules, which included TCF4, a key transcription factor involved in Wnt signaling. Activation of Wnt signaling upon mrhl RNA downregulation was demonstrated by beta-catenin nuclear localization, beta-catenin–TCF4 interaction, occupancy of beta-catenin at the promoters of Wnt target genes, and TOP/FOP-luciferase assay. Northwestern blot and RNA pulldown experiments identified Ddx5/p68 as one of the interacting proteins of mrhl RNA. Downregulation of mrhl RNA resulted in the cytoplasmic translocation of tyrosine-phosphorylated p68. Concomitant downregulation of both mrhl RNA and p68 prevented the nuclear translocation of beta-catenin. mrhl RNA was downregulated on Wnt3a treatment in Gc1-Spg cells. This study shows that mrhl RNA plays a negative role in Wnt signaling in mouse spermatogonial cells through its interaction with p68.